(3GdaQjO aj EYQGH GdbQBf GdeLjOs - (3GdoerfnJnLH rHf nCpHj GdYqR rHf QTjO, efJLH GdOjf CHh jhSa GdgePGfj, GdebQF,J (B643 (3g` s ((3Ydj Hf eWhY Hf TajY Hf fGLj Hf jMji Hf GdOZje GdHUQhj GdMfaj s)
(3ChdgG (B:s
(3EYQGH ShQI jhSa bhdg YRhLd GdQ Jdc(B: (3bO eVi GdcdGe Ydi EYQGH GdMQha ajeG Sda ef GdcJGH bHd s
(3BNQgG (B:s
(3ef EYQGH ShQI GdfGS, bhdg(B: (3hGdfGS ddLeY cGdJj aj GdHYhdI hGdYeheI, hGddg JYGdi CYde HcJGHg s
(3ajg VHWs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs